Flavour capsule cigarette use among US adult cigarette smokers. Issue 6 (23rd January 2018) - Emond, Jennifer A; Soneji, Samir; Brunette, Mary F; Sargent, James D
Abstract : Introduction: Flavour capsule cigarettes are a recent product worldwide, and little is known about the epidemiology of their use. We used data from a nationally representative survey to understand the sociodemographic characteristics of flavour capsule cigarette smokers and reasons for flavour capsule use. Methods: Data were from the nationally representative, U.S. Population Assessment of Tobacco and Health survey (2013–2014). Analyses included 7181 adults, aged 18–44 years, who were current or former established (≥100 lifetime cigarettes) cigarette smokers. Participants reported their usual brand of cigarettes which were classified as non-menthol, menthol or flavour capsule. Analyses assessed differences in participant demographics, smoking patterns and reasons for use by product type among those aged 18–24 years. Analyses were weighted to account for the survey design. Results: Flavour capsule cigarettes were the usual cigarettes among 9.4% of smokers aged 18–24 years and 6.0%, 3.7% and <1% of smokers aged 25–34, 35–44 and ≥45 years, respectively. Among smokers aged 18–24 year, a significantly higher percentage of Hispanic smokers (17.3%) usually used flavour capsule cigarettes versus non-Hispanic white (8.4%, P<0.05) and non-Hispanic black (3.2%, P<0.05) smokers. Flavour capsule use was associated with later onset of smoking and lower levels of nicotine dependency and flavour capsule users placed more emphasis on taste, lower price and pack design than menthol or non-menthol users. Conclusions: Flavour capsule cigarettes use is highest in young adults, particularly Hispanics. Young adult predominance, lower level of addiction symptoms and emphasis on pack design by flavour capsule users suggest that these products may be positioned as starter products.